894 Reducing the Duration of Antibiotic Course in a Neonatal Unit: Results of a Two Year Audit. (October 2012) - Pantazidou, A; Saeed, K; Struthers, S
Abstract : Background and Aims: Neonatal intensive care units (NICU) across the UK use different guidelines for the treatment of neonates at risk of sepsis. However, unless specific symptoms/risk factors for sepsis are present, antibiotics are usually stopped at 48 hours if blood culture (BC) results are negative. We aimed to determine whether it would be safe to stop antibiotics at 36 hours. Methods: We conducted a retrospective audit of all blood cultures over a two-year-period (2009–2011) from neonates at risk of or with suspected sepsis admitted to Winchester NICU - a medium-sized level 2 neonatal unit (3000 deliveries/year). BC were analysed with the automated BacT ALERT ® 3D Signature system, (Biomerieux, Durham, UK), using paediatric blood culture bottles (BacT/ALERT ® PF; incubated for a total of 5 days. Results: A total of 402 BC were identified and included in the analysis. Eighteen were positive (4.4%). The median time to BC positivity was 14.5 hours (25 th –75 th percentile:11.5–21.5 hours). There was no significant difference between the proportion of positive BC results at 36 and 48 hours (p=0.4857; odds ratio 0.178 (95% CI: 0.008–3.995)). Only two BC were positive after 36 hours; both were considered to be contaminants and did not changed management. Conclusions: Our data suggest that it is safe, in similar units using similar methods, to stop antibiotics after 36 hours if BC are negative. This would result in a substantial reduction in antibiotic use, invasive procedures and admission time, and thereby has significant implications for neonatal care.